Piaci információk szükségessége a mezőgazdaságban - Tomcsányi, Pál (Marketing & Menedzsment, 2017)
Sales possibilities for agricultural depend on the changing market to a greater extent than for most manufactured goods. That is why market information has a great importance in agriculture. The forms of information can be grouped as follows: • Report on the market situation indicating the concrete sales possibilities and price trends for a given product, with the purpose of giving a clearer picture of the market. • Short-term forecasts and yield estimates to facilitate secondary orientation. • Medium-term forecasts to make swifter changes in the product. • Long-term forecasts to determine the direction of national production and make it possible to draw up the state regulators required for the guidance of plant (enterprise) orientation. • Information on changes in forms of production must be available for both the medium-term and long-term range. • Medium-term and long-term range and quality development include technological possibilities which can incorporate ideas for the diversification of supply and ways of making up for shortages. Market research for agricultural firms can be carried out in the form of services provided by specialized institutes and must cover product specifications, local adaption of forms of production, comparison of production costs in different plants, possibilities for grouping branches of operation and local or seasonal demand for the product.